Metatranscriptomic and metataxonomic insights into the ultra-small microbiome of the Korean fermented vegetable, kimchi - Lee, Hae-Won; Yoon, So-Ra; Dang, Yun-Mi; Yun, Ji-Hyun; Jeong, Hoibin; Kim, Kil-Nam; Bae, Jin-Woo; Ha, Ji-Hyoung (Frontiers in Microbiology, 2022)
Presently, pertinent information on the ultra-small microbiome (USM) in fermented vegetables is still lacking. This study analyzed the metatranscriptome and metataxonome for the USM of kimchi. Tangential flow filtration was used to obtain a USM with a size of 0.2 μm or less from kimchi. The microbial diversity in the USM was compared with that of the normal microbiome (NM). Alpha diversity was higher in the USM than in NM, and the diversity of bacterial members of the NM was higher than that of the USM. At the phylum level, both USM and NM were dominated by Firmicutes. At the genus level, the USM and NM were dominated by Lactobacillus, Leuconostoc, and Weissella, belonging to lactic acid bacteria. However, regarding alpha diversity, the genus Akkermansia, belonging to the phylum Verrucomicrobia, was detected only in USM. Compared to NM, the USM showed a relatively higher ratio of transcripts related to “protein metabolism,” and the USM was suspected to be involved with the viable-but-nonculturable (VBNC) state. When comparing the sub-transcripts related to the “cell wall and capsule” of USM and NM, USM showed a proportion of transcripts suspected of being VBNC. In addition, the RNA virome was also identified, and both the USM and NM were confirmed to be dominated by pepper mild mottle virus (PMMoV). This study gained insights into the relationship between the potential metabolic activities of the USM of kimchi and the NM.